(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2024)
This research explains a local wisdom of the Iban ethnic group, that is, tattoo tradition. The practice of traditional tattooing in the Iban ethnic group is viewed as a unique culture because it has its own story and purpose. The symbolism of tattoos with elements of nature through the philosophy of “alam takambang jadi guru” is often used to express ideas and meaning about their culture and life. The objective of this study is to identify the relationship of nature as a teacher in the Iban ethnic group, discuss the importance of nature-based tattoo in the Iban ethnic group, and analyse the meaning of tattoo motifs in the Iban ethnic group. This research uses a qualitative approach through the methods of full observation and in-depth interview with informants. The result of the study found that the Iban ethnic group believe that nature teaches people to think creatively. Therefore, through nature, the Iban ethnic group produce creativity that uses natural resources of tattooing tradition to show local wisdom in their culture. Every event that occurs in the life of the Iban ethnic group cannot be separated from nature, that is, they believe that nature has spirit, soul, and strength that must be respected. The aesthetic value of the tattoo tradition can also be seen in the motifs produced with the inspiration of nature. Tattoo motifs with elements of nature are also considered to be able to inject elements of strength, symbolizing a person’s social status and achievements in various matters. This shows that nature acts as a teacher or as a guide for the Iban ethnic group in their daily life. Full text: PDF